2017
DOI: 10.1016/j.shaw.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Disorders in Northeast Lobstermen

Abstract: BackgroundThe objective of this study was to report on the prevalence of musculoskeletal pain in lobstermen in the northeast USA.MethodsCrews were randomly selected from those licensed to fish in Maine and Massachusetts and followed prospectively. The survey used a Nordic Musculoskeletal Questionnaire format to characterize musculoskeletal disorders.ResultsA total of 395 individuals participated. One half of the respondents reported low back pain. Back pain was attributed to or exacerbated by lobstering. Low b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 26 publications
(38 reference statements)
5
26
2
Order By: Relevance
“…This also explained the high prevalence of MSDs at multi-body sites (81%). When compared to studies among workers in different occupations, the prevalence of multi-site MSDs among WCs in this study were also higher (2,4,7,8,10).…”
Section: Situation Of Msdscontrasting
confidence: 58%
See 1 more Smart Citation
“…This also explained the high prevalence of MSDs at multi-body sites (81%). When compared to studies among workers in different occupations, the prevalence of multi-site MSDs among WCs in this study were also higher (2,4,7,8,10).…”
Section: Situation Of Msdscontrasting
confidence: 58%
“…The negative impact of the same act of physical labor is generally greater on females than males, which has been discussed above. The difference in the prevalence of MSDs between males and females was consistent across different occupations (3,4,6). Among demographic and work organization characteristics, no significant association between education level, age, years of service, working hours and MSDs were found, excluding the significant association between the working shift during the last three months and the Orebro mean score (p <0.01).…”
Section: Factors Related To Persistent Msdsmentioning
confidence: 71%
“…In one study, 35% of fishermen reported symptoms causing work interference within the last 12 months, with low back pain being the most common symptom . In a recent study of lobstermen in the Northeast, the annual rate of all reported occupational injuries was 50 per 100 full‐time workers with close to a third of these injuries requiring medical treatment, although many do not seek treatment . Fishing, like construction, is physically demanding, precarious, seasonal, and sometimes well‐paying.…”
Section: Discussionmentioning
confidence: 99%
“…MSDs are the leading cause of disability (2), result in impairing body function, affecting the workers' quality of life and reducing their working capability (3), which in turn will have significant economic ramifications for the workers (1). Although high prevalence of MSDs has been reported in various occupations (3)(4)(5)(6)(7)(8)(9)(10)(11), many employees with pain have to keep working for a living, hence continuously expose to specific occupational hazards which aggravate their pain conditions. Evidence on factors of persistent musculoskeletal pain is needed to develop effective prevention and control measures.…”
Section: Introductionmentioning
confidence: 99%